Specialization of the Reiterated Copies of the Heterodimeric Integration Host Factor Genes in Geobacter sulfurreducens - Andrade, Angel; Hernández-Eligio, Alberto; Tirado, Ana Lilia; Vega-Alvarado, Leticia; Olvera, Maricela; Morett, Enrique; Juárez, Katy (Frontiers in Microbiology, 2021)
Integration host factor (IHF) is a widely distributed small heterodimeric protein member of the bacterial Nucleoid-Associated Proteins (NAPs), implicated in multiple DNA regulatory processes. IHF recognizes a specific DNA sequence and induces a large bend of the nucleic acid. IHF function has been mainly linked with the regulation of RpoN-dependent promoters, where IHF commonly recognizes a DNA sequence between the enhancer-binding region and the promoter, facilitating a close contact between the upstream bound activator and the promoter bound, RNA polymerase. In most proteobacteria, the genes encoding IHF subunits (ihfA and ihfB) are found in a single copy. However, in some Deltaproteobacteria, like Geobacter sulfurreducens, those genes are duplicated. To date, the functionality of IHF reiterated encoding genes is unknown. In this work, we achieved the functional characterization of the ihfA-1, ihfA-2, ihfB-1, and ihfB-2 from G. sulfurreducens. Unlike the ΔihfA-2 or ΔihfB-1 strains, single gene deletion in ihfA-1 or ihfB-2, provokes an impairment in fumarate and Fe(III) citrate reduction. Accordingly, sqRT-PCR experiments showed that ihfA-1 and ihfB-2 were expressed at higher levels than ihfA-2 and ihfB-1. In addition, RNA-Seq analysis of the ΔihfA-1 and ΔihfB-2 strains revealed a total of 89 and 122 differentially expressed genes, respectively. Furthermore, transcriptional changes in 25 genes were shared in both mutant strains. Among these genes, we confirmed the upregulation of the pilA-repressor, GSU1771, and downregulation of the triheme-cytochrome (pgcA) and the aconitate hydratase (acnA) genes by RT-qPCR. EMSA experiments also demonstrated the direct binding of IHF to the upstream promoter regions of GSU1771, pgcA and acnA. PilA changes in ΔihfA-1 and ΔihfB-2 strains were also verified by immunoblotting. Additionally, heme-staining of subcellular fractions in ΔihfA-1 and ΔihfB-2 strains revealed a remarkable deficit of c-type cytochromes. Overall, our data indicate that at least during fumarate and Fe(III) citrate reduction, the functional IHF regulator is likely assembled by the products of ihfA-1 and ihfB-2. Also, a role of IHF controlling expression of multiple genes (other than RpoN-dependent) affects G. sulfurreducens physiology and extracellular electron transfer.